The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (Collection Ouvertures psychologiques. LMD, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."--Quatrième de couverture.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres